Ocean climate environment-torsional load coupling test device
By using a duplex stainless steel composite shell and an intelligent protective layer in the marine climate environment-torsional load coupling test equipment, real-time monitoring and dynamic adjustment of salt crystal adhesion can be achieved, solving the problem of rapid material performance degradation of the equipment in the marine environment, and achieving efficient protection and extended life of the equipment.
Patent Information
- Application Number
- CN202511113415.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-11
- Publication Date
- 2025-10-10
- Estimated Expiration
- 2045-08-11
AI Technical Summary
The existing marine climate environment-torsional load coupling test equipment is exposed to harsh environments such as high temperature, high humidity, high salt spray and frequent dry/wet alternating cycles. The material performance degrades rapidly, and traditional coatings are difficult to effectively extend the service life.
It adopts a duplex stainless steel composite shell, embedded with distributed optical fiber sensors and shape memory alloy mesh and piezoelectric ceramic drivers arranged in an interlaced manner, combined with a gradient protective layer design, to monitor and dynamically adjust the salt crystal adhesion in real time, and optimize the protection mode through a data fusion module.
It significantly improves the service life of equipment in marine climate environment, reduces the risk of cracking and failure of traditional rigid protective structures, and enhances the stability of corrosion resistance and protection efficiency.
Smart Images

Figure CN120594276B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of structural static balance testing, in particular to a marine climate environment-torsion load coupling testing device. Background Art
[0002] Application number CN201821424018.4 discloses a marine climate environment-torsion load coupling test device, comprising a frame structure with a clamping mechanism disposed on the upper portion of the frame structure. The clamping mechanism is connected to a servo-torsion fatigue system, which is in turn connected to a hydraulic power system, which is in turn connected to an environmental test control system. The clamping mechanism and the upper portion of the frame structure are hollowed out on all four sides and exposed to the marine atmosphere. The servo-torsion fatigue system, signal detection unit, power system, and lower portion of the frame structure are disposed in a sealed chamber with controllable temperature and humidity. This test device exhibits excellent stability, coordination, waterproofness, and reliability, and can be used in marine atmospheres for a long time.
[0003] During torsional load testing, the main and countershafts clamp the shaft under test and rotate in opposite directions, inevitably increasing their deformation. Furthermore, testing in a marine climate, where the equipment is subject to harsh environmental corrosion such as high temperature, high humidity, high salt spray, and frequent dry / wet cycles, coupled with repeated fatigue loads such as tension and torsion, significantly impacts the mechanical properties of the material, significantly exceeding the combined effects of environmental corrosion and fatigue alone. Therefore, simply modifying the primary material and applying an organic coating to it is unlikely to significantly extend the equipment's service life. Summary of the Invention
[0004] In order to overcome the defects in the prior art, the purpose of the present invention is to provide a marine climate environment-torsion load coupling test equipment to solve the problems raised in the above background technology.
[0005] To achieve the above objectives, the present invention provides a marine climate environment-torsion load coupling test equipment, comprising a test bench and a main shaft box and a counter shaft box installed at both ends of the test bench, wherein the main shaft box and the counter shaft box are both coaxially installed with a claw shaft for clamping the shaft to be tested and twisting it in the opposite direction;
[0006] It includes a composite shell coaxially nested with the claw shaft. The composite shell is made of duplex stainless steel and is composited with the following components from the inside to the outside:
[0007] A monitoring layer, formed by a distributed optical fiber sensor array, is used to monitor shell deformation data in real time; the monitoring layer is located on the inner surface of the cylinder;
[0008] The response layer, composed of a staggered arrangement of shape memory alloy mesh and piezoelectric ceramic actuators, dynamically adjusts the salt crystal adhesion according to strain data;
[0009] The protective layer is composed of a transition layer, a deformation layer and a display layer from the inside to the outside, wherein the transition layer is a nickel-aluminum intermetallic compound layer, the deformation layer is an electroactive polymer base layer, and the display layer is a microcapsule layer; the response layer and the protective layer are located on the outer surface of the cylinder;
[0010] The data fusion module synchronously processes the torque load data and the salinity and humidity parameters collected by the environmental sensor to dynamically optimize the working mode of the protective layer.
[0011] As a further improvement of the present technical solution, the distributed optical fiber sensors are arrayed by spirally winding around the inner wall of the cylinder.
[0012] As a further improvement of the present technical solution, the shape memory alloy mesh is made of a Ni-Ti-Cu ternary alloy, the mesh has a hexagonal topological configuration, a side length of 2-3 mm, and the phase change temperature is set to 25°C±3°C; the shape memory alloy mesh is fixed to the outer surface of the cylinder by laser spot welding, and the welding point spacing is 5 mm.
[0013] As a further improvement of the technical solution, the piezoelectric ceramic driver is embedded in the electroactive polymer base layer, the circuit is connected using conductive silver glue, and the surface of the deformation layer is provided with a micro-nano structure.
[0014] As a further improvement of the present technical solution, the micro-nano structure is a photocatalytic TiO2 / Ag nano-coating, which forms a crater-shaped protrusion with a diameter of 50-200 μm, with carbon nanotube bundles embedded inside, and realizes dynamic adjustment of the height direction of 0-50 μm through a piezoelectric ceramic driver.
[0015] As a further improvement of the present technical solution, the deformation layer is made of polyvinylidene fluoride / graphene composite material, the piezoelectric coefficient d33 of which is ≥25pC / N, and forms an energy recovery circuit with the energy storage capacitor.
[0016] As a further improvement of the present technical solution, the display layer comprises a pH-sensitive color-changing material and a benzotriazole derivative corrosion inhibitor, and the capsule rupture threshold pressure is 5-8 MPa.
[0017] As a further improvement of the present technical solution, the data fusion module integrates a finite element simulation unit to calculate the stress corrosion factor under torque-humidity-salinity multi-field coupling in real time.
[0018] As a further improvement of the present technical solution, a sealing group is provided at the joint between the composite shell port and the claw shaft. The sealing group is formed by connecting a male sealing ring and a female sealing ring made of silicone material. The inside of the male sealing ring and the female sealing ring are both nested with guide slip rings for connecting the internal and external circuits.
[0019] As a further improvement of the present technical solution, one end of the male sealing ring is provided with a sealing block protruding in a circular shape with equal intervals, and the outer surface of one end of the female sealing ring is provided with a plurality of card grooves in a circular shape with equal intervals, and the plurality of sealing blocks are correspondingly engaged with the plurality of card grooves. The outer end of one of the guide slip rings is provided with cards in a circular shape with equal intervals, and the outer end of the other guide slip ring is provided with a plurality of card slots in a circular shape with equal intervals, and the plurality of cards are correspondingly engaged with the plurality of card slots.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. This marine climate environment-torsional load coupling test equipment has a composite shell nested and sealed outside the main shaft and secondary shaft. It uses duplex stainless steel as the base material and achieves a synergistic enhancement of the corrosion resistance of the base material and the bonding strength of the coating through a gradient protective layer design. The corrosion resistance is higher than that of ordinary steel, which increases the service life of the overall structure in a marine climate environment.
[0022] 2. The marine climate environment-torsion load coupling test equipment, through the intelligent coupling control of the shape memory alloy mesh and the piezoelectric ceramic driver, completes the dynamic adaptive adjustment of the protective layer curvature with the torque load and environmental salinity, thereby achieving the effect of reducing the surface stress concentration factor and the fluctuation amplitude of the protection efficiency, and reducing the cracking and failure of traditional rigid protective structures under dynamic loads. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings described herein are for illustrative purposes only and are not intended to limit the scope of the present invention in any way. In addition, the shapes and proportional dimensions of the various components in the drawings are merely illustrative and are used to help understand the present invention, and are not intended to specifically limit the shapes and proportional dimensions of the various components of the present invention. Those skilled in the art will select various possible shapes and proportional dimensions to implement the present invention according to the specific circumstances under the guidance of the present invention.
[0024] Figure 1 It is a schematic diagram of the overall structure of the present invention;
[0025] Figure 2 It is a plan view of the radial cross-section structure of the composite shell of the present invention;
[0026] Figure 3 It is a plan view of the protective layer structure of the present invention;
[0027] Figure 4 This is a schematic diagram of the sealing assembly structure of the present invention;
[0028] Figure 5 This is a schematic diagram of the assembly structure of the guide slip ring of the present invention;
[0029] Figure 6 This is a diagram showing the sealing assembly of the present invention;
[0030] The meaning of each number in the figure is:
[0031] 100. Test bench; 110. Slide rail;
[0032] 200, spindle box; 210, claw shaft; 220, transmission screw;
[0033] 300, slide; 310, countershaft box;
[0034] 400, composite shell; 410, cylinder; 420, monitoring layer; 430, response layer;
[0035] 440, protective layer; 441, transition layer; 442, deformation layer; 443, display layer;
[0036] 450, sealing group; 451, male sealing ring; 4511, sealing block; 452, female sealing ring; 4521, slot; 453, guide ring; 4531, bayonet; 4532, card. DETAILED DESCRIPTION
[0037] The details of the present invention can be more clearly understood in conjunction with the accompanying drawings and the description of the specific embodiments of the present invention. However, the specific embodiments of the present invention described herein are for illustrative purposes only and are not to be construed as limiting the present invention in any way. Under the guidance of the present invention, any possible variations of the present invention conceived by skilled artisans should be considered within the scope of the present invention. The terms "mounted" and "connected" should be understood broadly, meaning direct connection as well as indirect connection through an intermediary.
[0038] The terms "central axis," "vertical," "horizontal," "front," "back," "up," "down," "left," "right," "top," "bottom," "inside," and "outside" used herein to indicate positions or location relationships are based on the positions or location relationships shown in the accompanying drawings and are intended solely to facilitate and simplify the description of the present invention. They do not indicate or imply that the devices or components referred to must have a specific orientation, be constructed, or operate in a specific orientation. Therefore, they should not be construed as limiting the present invention. Furthermore, in the description of the present invention, "several" means two or more, unless otherwise specifically defined.
[0039] See also Figures 1-6As shown, the present invention provides a marine climate environment-torsion load coupling test equipment, including a test bench 100 and a main spindle box 200 and a counter spindle box 310 installed at both ends of the test bench 100, and the main spindle box 200 and the counter spindle box 310 are coaxially installed with a claw rotating shaft 210 for clamping the shaft to be tested and twisting it in the opposite direction; a slide rail 110 is installed on the top surface of the test bench 100, and a slide 300 is slidably clamped on the slide rail 110, and the counter spindle box 310 is fixedly connected to the top surface of the slide 300 by bolts, and a servo motor is installed in the bottom of the main spindle box 200 and its output shaft end is coaxially connected with a transmission screw 220, and the transmission screw 220 is threadedly connected to the slide 300, and is used to drive the counter spindle box 310 and the main spindle box 200 to adjust the clamping distance. The above is the existing technology and will not be repeated here.
[0040] The test table 100, the main spindle box 200 and the counter spindle box 310 housing, the slide 300, the claw shaft 210 and the transmission screw 220 are all made of duplex stainless steel (2205 DSS). The specific composition of duplex stainless steel is 22% Cr, 5% Ni, 3% Mo, 0.17% N. Duplex stainless steel has a dual-phase structure of austenite and ferrite and is resistant to Cl. - The corrosion resistance is higher than 304 stainless steel.
[0041] Specifically, the claw shaft 210 is coaxially nested with a composite shell 400. The composite shell 400 is made of a cylinder 410 made of duplex stainless steel and is composited with the following from the inside to the outside:
[0042] The monitoring layer 420 is formed by a distributed optical fiber sensor array and is used to monitor the shell deformation data in real time; the monitoring layer 420 is located on the inner surface of the cylinder 410;
[0043] The response layer 430 is composed of a staggered arrangement of shape memory alloy mesh and piezoelectric ceramic actuators, which dynamically adjusts the adhesion of salt crystals according to strain data;
[0044] The protective layer 440 is composed of a transition layer 441, a deformation layer 442 and a display layer 443 from the inside to the outside. The transition layer 441 is a nickel-aluminum intermetallic compound layer, which is produced by arc ion plating, with a target current of 80A, a bias voltage of -150V, an Ar gas pressure of 0.5Pa, and a thickness of 50-80μm; the deformation layer 442 is an electroactive polymer base layer, which is produced by electrostatic spraying, a voltage of 80kV, and a thickness of 0.8-1.2mm; the display layer 443 is a microcapsule layer, which is produced by microfluidic co-deposition technology and has a thickness of 200-300μm; the response layer 430 and the protective layer 440 are located on the outer surface of the cylinder 410; the composite shell 400 uses duplex stainless steel as the base material, and through the gradient protective layer design and multi-interface enhancement technology, the corrosion resistance of the base material is improved to be better than that of ordinary steel.
[0045] Furthermore, the distributed optical fiber sensor is arrayed by spirally winding the inner wall of the cylinder 410, and the sensor gap is filled with UV-curing epoxy acrylate, so that the winding pitch and the thread lead generated by the torque loading maintain a certain proportional relationship, thereby improving the strain monitoring resolution and accurately measuring the torque data.
[0046] Specifically, the shape memory alloy mesh is made of a Ni-Ti-Cu ternary alloy, the mesh has a hexagonal topology configuration, a side length of 2-3 mm, and a phase change temperature set to 25°C ± 3°C to maintain the surface curvature; the shape memory alloy mesh is fixed to the outer surface of the cylinder 410 by laser spot welding, and the welding point spacing is 5 mm.
[0047] Specifically, the piezoelectric ceramic driver is embedded in the electroactive polymer substrate, and the circuit is connected using conductive silver glue. The surface of the deformation layer 442 is provided with a micro-nano structure. The micro-nano structure is a photocatalytic TiO2 / Ag nano-coating, forming a crater-like protrusion with a diameter of 50-200μm, with a carbon nanotube bundle embedded inside. The piezoelectric ceramic driver achieves dynamic adjustment of the height direction from 0-50μm. The surface topology is automatically optimized according to the salt spray concentration to reduce the adhesion of salt crystals.
[0048] Shape memory alloy mesh (221) control, temperature excitation: adjust the current (0-5A) according to the torque gradient ▽T to trigger the phase change: I=k1·|▽T|+k2·S 0.3 ,
[0049] k1=0.2A / (N·m / m), k2=0.05A / (mg / L) 0.3 ; Deformation output: mesh side length change ΔL=0.15·ΔT+0.08·ΔS (mm).
[0050] Furthermore, the deformation layer 442 is made of a polyvinylidene fluoride / graphene composite material with a piezoelectric coefficient d33 ≥ 25pC / N, which forms an energy recovery circuit with the energy storage capacitor; thus achieving a self-powered efficiency for the protective function of the composite shell 400 and reducing dependence on external power supply;
[0051] Piezoelectric ceramic driver (222) control, voltage-displacement relationship:
[0052] d=0.5·V+0.1·ln(S / S0)(μm / V);
[0053] The maximum driving voltage is 150V, and the corresponding surface curvature radius adjustment range is R=200-500mm.
[0054] Furthermore, the display layer 443 contains a pH-sensitive color-changing material and a benzotriazole derivative corrosion inhibitor, and the capsule rupture threshold pressure is 5-8 MPa, so that the color change warning visible to the naked eye occurs earlier than the electrochemical corrosion; when the local pH value is monitored to be greater than 8.5, the electric field activation field strength is triggered to 3 kV / mm, the microcapsule ruptures and releases the corrosion inhibitor, the response time is less than 30 s, and the polarization resistance and corrosion current density are measured in real time by the electrochemical workstation.
[0055] Specifically, the data fusion module synchronously processes torque load data and salinity and humidity parameters collected by environmental sensors to dynamically optimize the working mode of the protective layer 440. The data fusion module integrates a finite element simulation unit to calculate the stress corrosion factor under the torque-humidity-salinity multi-field coupling in real time. A strain-type torque sensor is used to collect the following data in real time: torque value T (0-50N·m), load frequency f (0-5Hz), and torsional deformation ε (με).
[0056] The environmental sensor group integrates multi-parameter probes for simultaneous monitoring: salinity S (mg / L, accuracy ±0.5%), humidity φ (%, accuracy ±1%), and temperature θ (°C, accuracy ±0.3°C);
[0057] Establish the ternary control equation of torque load-environmental parameters-protection effectiveness:
[0058] η=k1· T / τ y +k2·ln(S / S0)+k3·e (φ / φc) ;
[0059] η: protection efficiency (%); T: real-time torque (N·m); τ y : material yield torque threshold (N·m); S: environmental salinity (mg / L); S0: reference salinity (35 mg / L, simulating standard seawater); φ: environmental relative humidity (%); φ c : Critical humidity threshold (80%); k1, k2, k3 weight coefficients.
[0060] Determine the coefficients by orthogonal test method (laboratory conditions: ISO 9227 salt spray test chamber + torque loading platform):
[0061] .
[0062] Calibration results: k1=0.85, k2=-2.3, k3=-1.7, τ y =50; goodness of fit: R²=0.987.
[0063] Typical working condition verification:
[0064] Working condition 1: Conventional marine environment, calculated η=0.85×15 / 50-2.3×ln(35 / 35)-1.7×e (75 / 80) =0.255-0-1.7×2.117=89.1%, measured value: 88.7%, error 0.4%;
[0065] Working condition 2: high torque + high salt spray, the calculated η = 73.2%, the measured value: 72.5%, the error is 0.7%;
[0066] Working condition 3: extreme humidity, calculated η = 82.7%, measured value: 81.9%, error 0.8%.
[0067] Dynamic response verification:
[0068] Under the torque fluctuation condition (frequency 0.5Hz), the equation prediction is compared with the actual measurement:
[0069] .
[0070] Dynamic response consistency: phase delay <0.1s, amplitude error <1.2%.
[0071] Comparison of technical effects, compared with the traditional static protection solution (control group):
[0072] .
[0073] Conclusion verification:
[0074] The equation can quantitatively predict the protection efficiency with an error within ±1%;
[0075] The dynamic coupling mechanism increases the protection system's response speed to torque changes by five times;
[0076] The weight coefficient k2 / k3=1.35 proves that the influence of salinity is higher than that of humidity, which is consistent with the electrochemical corrosion mechanism.
[0077] In addition, a sealing group 450 is provided at the joint between the port of the composite shell 400 and the claw shaft 210, which seals the claw shaft 210 and resists corrosion from seawater moisture; the sealing group 450 is formed by connecting a male sealing ring 451 and a female sealing ring 452 made of silicone material, and the inside of the male sealing ring 451 and the female sealing ring 452 are both nested with a guide slip ring 453 for connecting the internal and external circuits, so that the optical fiber sensor, piezoelectric ceramic driver and environmental sensor on the composite shell 400 can be powered and work.
[0078] Furthermore, one end of the male sealing ring 451 is provided with a sealing block 4511 protruding in a circular shape with equal intervals, and the outer surface of one end of the female sealing ring 452 is provided with a plurality of card grooves 4521 in a circular shape with equal intervals. The plurality of sealing blocks 4511 are correspondingly engaged with the plurality of card grooves 4521. The outer end of one of the guide slip rings 453 is provided with a card 4532 in a circular shape with equal intervals, and the outer end of the other guide slip ring 453 is provided with a plurality of card slots 4531 in a circular shape with equal intervals. The plurality of cards 4532 are correspondingly engaged with the plurality of card slots 4531, thereby forming a staggered card connection, which makes the connection tighter and ensures the sealing and conductive properties.
[0079] It should be noted that the above embodiments are intended only to illustrate the technical concepts and features of the present invention. Their purpose is to enable those skilled in the art to understand the contents of the present invention and implement them accordingly. They are not intended to limit the scope of protection of the present invention. Any equivalent changes or modifications made in accordance with the spirit and substance of the present invention are intended to be encompassed within the scope of protection of the present invention.
Claims
1. A marine climate environment-torsion load coupling test device, comprising a test bench (100) and a main shaft box (200) and a counter shaft box (310) installed at both ends of the test bench (100), wherein the main shaft box (200) and the counter shaft box (310) are both installed with a claw shaft (210) at the coaxial position, for clamping the shaft to be tested and reversely twisting it; It is characterized by: The composite shell (400) is coaxially nested with the claw rotating shaft (210). The composite shell (400) is made of a cylinder (410) made of duplex stainless steel and is composited with the following components from the inside to the outside: A monitoring layer (420) is formed by a distributed optical fiber sensor array and is used to monitor shell deformation data in real time; the monitoring layer (420) is located on the inner surface of the cylinder (410); The response layer (430) is composed of a shape memory alloy mesh and a piezoelectric ceramic actuator arranged in an interlaced manner, and dynamically adjusts the salt crystal adhesion according to the strain data; The protective layer (440) is composed of a transition layer (441), a deformation layer (442), and a display layer (443) from the inside to the outside, wherein the transition layer (441) is a nickel-aluminum intermetallic compound layer, the deformation layer (442) is an electroactive polymer base layer, and the display layer (443) is a microcapsule layer; the response layer (430) and the protective layer (440) are located on the outer surface of the cylinder (410); The data fusion module synchronously processes the torque load data and the salinity and humidity parameters collected by the environmental sensor to dynamically optimize the working mode of the protective layer (440); The piezoelectric ceramic driver is embedded in the electroactive polymer base layer, and a conductive silver glue is used to connect the circuit. The surface of the deformation layer (442) is provided with a micro-nano structure; The data fusion module integrates a finite element simulation unit to calculate the stress corrosion factor under the torque-humidity-salinity multi-field coupling in real time; through the intelligent coupling control of the shape memory alloy mesh and the piezoelectric ceramic driver, the curvature of the protective layer is dynamically adaptively adjusted according to the torque load and environmental salinity.
2. The marine climate environment-torsion load coupling test equipment according to claim 1, characterized in that: The distributed optical fiber sensors are arrayed by spirally winding around the inner wall of the cylinder (410).
3. The marine climate environment-torsion load coupling test equipment according to claim 2, characterized in that: The shape memory alloy mesh is made of a Ni-Ti-Cu ternary alloy, has a mesh with a hexagonal topology, a side length of 2-3 mm, and a phase transition temperature set at 25°C±3°C; the shape memory alloy mesh is fixed to the outer surface of the cylinder (410) by laser spot welding, and the welding point spacing is 5 mm.
4. The marine climate environment-torsion load coupling test equipment according to claim 3, characterized in that: The micro-nano structure is a photocatalytic TiO2 / Ag nano-coating, which forms a crater-shaped protrusion with a diameter of 50-200 μm, with carbon nanotube bundles embedded inside, and realizes dynamic adjustment of 0-50 μm in height direction through a piezoelectric ceramic driver.
5. The marine climate environment-torsion load coupling test equipment according to claim 4, characterized in that: The deformation layer (442) is made of a polyvinylidene fluoride / graphene composite material, the piezoelectric coefficient d33 of which is ≥25pC / N, and forms an energy recovery circuit with the energy storage capacitor.
6. The marine climate environment-torsion load coupling test equipment according to claim 5, characterized in that: The display layer (443) comprises a pH-sensitive color-changing material and a benzotriazole derivative corrosion inhibitor, and the capsule rupture threshold pressure is 5-8 MPa.
7. The marine climate environment-torsion load coupling test equipment according to claim 6, characterized in that: A sealing group (450) is provided at the socket connection between the port of the composite shell (400) and the claw shaft (210). The sealing group (450) is formed by connecting a male sealing ring (451) and a female sealing ring (452) made of silicone material. A guide slip ring (453) for connecting the internal and external circuits is embedded inside the male sealing ring (451) and the female sealing ring (452).
8. The marine climate environment-torsion load coupling test equipment according to claim 7, characterized in that: One end of the male sealing ring (451) is provided with a sealing block (4511) protruding in a circular shape at equal intervals, and the outer surface of one end of the female sealing ring (452) is provided with a plurality of card grooves (4521) in a circular shape at equal intervals, and the plurality of sealing blocks (4511) are correspondingly engaged with the plurality of card grooves (4521), and the outer end of one of the guide slip rings (453) is provided with a card (4532) in a circular shape at equal intervals, and the outer end of the other guide slip ring (453) is provided with a plurality of card slots (4531) in a circular shape at equal intervals, and the plurality of card slots (4532) are correspondingly plugged into the plurality of card slots (4531).
Citation Information
Patent Citations
Mechanical fault monitoring method for photoelectric composite submarine cable
CN110296885A
Marine climate environment - torsion load coupling test device
CN208621311U